Species diversification, livestock production and income of the poor in the Indian State of Andhra Pradesh - Akter, S.; Farrington, John; Deshingkar, P.; Rao, L.; Freeman, H.A. (2007)
This paper investigates the factors associated with private sector smallholder livestock and the associated income of the poor in the Indian States of Andhra Pradesh. The data used are drawn from the Livelihood Options Study led by the Overseas Development Institute, London, specifically the Census Survey 2001/2 and Panel Survey of early 2005. Poorer households depend disproportionally on livestock. Important changes were noted; the average size of any single species declined considerably in the five year period beginning from 1996/7, the number of farms keeping the species rose in the 1996/7 to 2001/2 period but dropped in the recent 2001/2 to 2003/4 period. The poorer households kept fewer small ruminants and poultry in the latter period but richer households kept more. This might suggest that the technology is shifting towards what the better off can afford like the intensive poultry keeping, and that they have better access to certain resources such as crop residues. On the other hand, policies such as the ban on grazing by goats will also have affected the poor more since they rely on open-grazing methods. Farmers identified shock/stress variables and natural environment as important for the decrease in livestock population. Livestock act as a very real means of smoothing income by allowing debts to be repaid, farm inputs and medical treatment to be purchased, and dowry to be paid. More than 22% of the farmers mentioned disease problems as a cause of the decline in livestock population. This problem needs to be addressed, possibly through public-private partnership arrangements as are being tried in other countries.